1998
DOI: 10.1046/j.1365-2982.1998.00120.x
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic dysfunction in patients with achalasia of the oesophagus

Abstract: It has been suggested that achalasia is associated with extraoesophageal sympathetic and parasympathetic dysfunction. In a prospective study we applied conventional ultrasonography and duplex sonography to investigate basal and postprandial peak systolic velocity (PSV), pulsatility index (PI) and resistance index (RI) of superior mesenteric artery and PSV of portal vein in nine patients with achalasia and 10 healthy controls (study I). In addition, in eight of these patients autonomic nervous function was inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…A study has suggested that complement activation is involved in the autoimmune pathogenesis of achalasia [11] . Achalasia is associated with extra esophageal autonomic nervous dysfunction that involves cardiovascular and papillary function as well as regulation of mesenteric arterial blood flow [12] . Some investigators have proposed that achalasia may result from chronic infections with herpes zoster or measles viruses, but modern studies have not confirmed an association between achalasia and any recognized viral disease [13,14] .…”
Section: Introductionmentioning
confidence: 99%
“…A study has suggested that complement activation is involved in the autoimmune pathogenesis of achalasia [11] . Achalasia is associated with extra esophageal autonomic nervous dysfunction that involves cardiovascular and papillary function as well as regulation of mesenteric arterial blood flow [12] . Some investigators have proposed that achalasia may result from chronic infections with herpes zoster or measles viruses, but modern studies have not confirmed an association between achalasia and any recognized viral disease [13,14] .…”
Section: Introductionmentioning
confidence: 99%
“…An association with HLA epitopes has previously been reported and is investigated further by de la Concha et al 94 . A number of reports confirm that achalasia is not just a disease affecting the esophagus but can be linked to abnormalities in the cricopharyngeus, 95 stomach, 96 colon, 97 cardiovascular system, 98 and eye 99 . Several unusual complications have been reported, including cardiac compression 100 and tracheal obstruction 101 .…”
Section: Esophageal Motilitymentioning
confidence: 84%
“…The studies on extra‐oesophageal autonomic dysfunction in idiopathic achalasia reported contradictory results. The autonomic cardiovascular reflexes in patients with idiopathic achalasia are altered in some studies, 16–19 but in others they are normal 20–22 . Eckardt et al .…”
Section: Discussionmentioning
confidence: 99%
“…Von Herbay et al . observed statistical differences of parasympathetic tests between eight patients with achalasia and eight healthy volunteers, 17 but they also included patients with advanced age (until 81 years). The study of Ohlsson et al 19 .…”
Section: Discussionmentioning
confidence: 99%